Heat Transfer Intern Coefficient Determination in the Process of Solar Still. (June 2019) - Chávez, S; Terres, H; Lizardi, A; López, R; Lara, A
Abstract: In this work, a study of internal heat transfer coefficients is performed in a solar still of a slope is presented, when it operated with brine. The estimate is based on the experimental observation of the solar still for 4 different initial volumes (2, 4, 6 y 8 L), under the climatic conditions of the city of Mexico. The internal coefficients to evaluate are: convection, evaporation and radiation through the use of the thermal model proposed by Kumar and Tiwari. As a result it was found that the internal coefficient more representative in the process of solar distillation is the evaporation ( h E, w-g ), reaching a maximum of 30 W/m 2 K, the coefficients of convection ( h c, w-g ), and radiation ( h R, w-g ), attained values of 2.5 W/m 2 K and 4 W/m 2 K respectively. It was also noted that as the initial volume of brine increases, the internal heat transfer coefficients decrease.